Microvesicles carrying EV71 virions cross BBB through endocytic pathway to induce brain injury - Xiaoyan Tian; Bingxin Liu; Linrun Li; Meng Yuan; Qiao You; Rui Zhang; Deyan Chen; Min Cheng; Nan Zheng; Miao He; Zhiwei Wu (Cell Communication and Signaling)
Abstract Enterovirus 71 (EV71) is a major etiologic pathogen for hand-foot-and-mouth disease (HFMD) in young children. Severe cases of EV71 infection could lead to neurological complications and even death, while the mechanism inducing neurological complications remains poorly understood. In this study, we firstly proved that microvesicles (MVs) could carry EV71 virions and mediate a higher efficiency in infection. Utilizing an in vitro blood-brain barrier (BBB) model, we observed that MVs containing virions (MVsEV71) could cross the BBB with greater efficiency compared to EV71 alone. Through in vivo imaging, we confirmed the ability of MVs to cross the BBB. qPCR assays showed a higher copy number of EV71 in both blood and brain samples in the mice treated with MVsEV71 compared to those treated with free EV71. Also, our investigation unveiled that MVsEV71 infection of animals induced cerebral hemorrhage and more severe inflammatory infiltration in the brain compared to animals infected by EV71 in vivo. Furthermore, we found a reduction in the expression of junction proteins such as zonula occludens-1 (ZO-1) and occludin. Moreover, the uptake of MVs by brain cells was examined using chemical inhibitor to block the endocytic pathway. Our experiments elucidated that the internalization of MVs occurred via a non-clathrin-dependent mechanism and a portion of the internalized MVs proceeded to enter lysosomes. In addition, we identified damaged mitochondria as the “cargo” of MVs, which facilitated MVsEV71 crossing the BBB and inducing cellular apoptosis. Meanwhile, MVsEV71 crossing the BBB further induced mitochondrial damaged and activated NOX4-derived ROS pathway in U251 cells. Taken together, these findings suggested that MVs transported EV71 virions across the BBB, while damaged mitochondria facilitated this process and aggravated the brain injury. Overall, these observations provide new insights into EV71-induced neurogenic complications and present a novel therapeutic target for the treatment of viral encephalitis.